Keteladanan Guru Agama Dalam Membentuk Akhlakul Karimah - Sufinatin Aisida; Abd Rohman Wahid (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2021)
This study aims to analyze the role model of religious teachers in shaping morals at MTs Darul Barokah Surabaya. Through a qualitative descriptive approach, this study concludes that the formation of student character can be through the example displayed by educators. Exemplary has an important meaning in the educational process, if the teacher has a good temperament then the students also have good morals, and vice versa. A teacher must be able to be a role model for his students, not only providing subject matter but also being able to demonstrate good behavior so that it can be applied in everyday life in madrasas and society.